Good day! I'm currently having an exercise on partial fractions... I know the basic of different methods in separating a fraction into smaller parts but I got confused when I encountered this one$$\frac {(n + 1)^2 (t^{2n})}{(t^{2n+2} - 1)^{2}}$$ is there any way on how to deal with this 2 variable fraction? I tried wolfram online calculator and I got this $$\frac{n^2}{(4t^2 (t^{n+1}-1) )}- \frac {n^2}{(4t^2 (t^{n+1}+1) )}+ \frac{n^2}{(4t^2 (t^{n+1}-1)^2 )}+ \frac {n^2}{(4t^2 (t^{n+1}+1)^2 )}+ \frac{n}{(2t^2 (t^{n+1}-1) )}- \frac{n}{(2t^2 (t^{n+1}+1) )}+ \frac{n}{(2t^2 (t^{n+1}-1)^2 )}+ \frac {n}{(2t^2 (t^{n+1}-1)^2 )}+ \frac {1}{(4t^2 (t^{n+1}-1) )}- \frac{1}{(4t^2 (t^{n+1}+1) )}+ \frac{1}{(4t^2 (t^{n+1}-1)^2 )}+ \frac {1}{(4t^2 (t^{n+1}+1)^2 }$$

But I'm not onlu interested to the answer alone but to the solution itself... any idea would be a great help... thanks!


You want to re-express $x$ in

$x = \displaystyle\frac {(n + 1)^2 (t^{2n})}{(t^{2n+2} - 1)^{2}}$

Write $x = \dfrac{(n + 1)^2}{t^2} \cdot \dfrac{t^{2n+2}}{(t^{2n+2} - 1)^{2}}$

Then put $u = t^{n+1}$ to get $x = \dfrac{(n + 1)^2}{t^2} \cdot \dfrac{u^2}{(u^2 - 1)^{2}} \tag{1}$

and then because we are dealing with repeated factors

$\dfrac{u^2}{(u^2 - 1)^2} = \dfrac{u^2}{(u+1)^2(u-1)^2} = \dfrac{A}{u+1} + \dfrac{B}{(u+1)^2} + \dfrac{C}{u-1} + \dfrac{D}{(u-1)^2} \tag{2}$.

Then multiply the last equation through by the full denominator to get

$u^2 = A(u+1)(u-1)^2+B(u-1)^2+C(u+1)^2(u-1)+D(u+1)^2 \tag{3}$

Now evaluate at $u=-1, u=1$ (some terms are zero) to get the two equations

$\begin{align} 1 &= 4B \\ 1 &= 4D \end{align}$

whence $\boxed{B=D=\frac{1}{4}}$.

Taking the derivative of (3) wrt $u$:

$2u = A[(u-1)^2+2(u+1)(u-1)]+2B(u-1)+C[2(u+1)(u-1)+(u+1)^2]+2D(u+1) \tag{4}$

Evaluate at $u=-1, u=1$ to get the two equations:

$\begin{align} -2 &= 4A - 4B &= 4A - 1 \\ 2 &= 4C + 4D &= 4C + 1 \end{align}$

whence $\boxed{A=-\frac{1}{4}, C=\frac{1}{4}}$


$\dfrac{u^2}{(u^2 - 1)^2} = \dfrac{1}{4} \Bigg\{\cdot \dfrac{-1}{u+1} + \dfrac{1}{(u+1)^2} + \dfrac{1}{u-1} + \dfrac{1}{(u-1)^2}\Bigg\} \tag{5}$

Now substitute (5) into (1) then apply $u=t^{n+1}$ to get the complete expression for $x$.

  • $\begingroup$ thank a lot @Marconius taking the derivative does not come into my mind... tnx a lot! $\endgroup$ – rosa Jul 13 '15 at 15:10

i think:

$ (n+1)^2 \frac{t^{2n}}{(t^{n+1}-1)(t^{n+1}+1)} $

$ u=t^n $

$ (n+1)^2 \frac{u^2}{(u^2-1)^2(u^2+1)^2} $

now, first decompose this , and then return to original variable, t, and decompose again the rest of terms

or again change the variable as below:

$ z=u^2 $

and then do the aforementioned sequential decomposition!


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.